Feasibility of flow-based optical provisioning in GEANT - DOYLE, LINDA; O'MAHONY, DONAL EDWARD; Ruffini, M. (Optical Society of America, 2007)
We present a novel network architecture that establishes dynamic optical paths by analyzing local network traffic. We demonstrate its feasibility and effectiveness through a network analysis using real traces collected from the pan-European GEANT network.
PUBLISHED
Keywords: network analysis